2021
DOI: 10.1002/jclp.23246
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting psychological pain avoidance and decision‐making bias as key predictors of suicide attempt in major depressive disorder—A novel investigative approach using machine learning

Abstract: Objective Predicting suicide is notoriously difficult and complex, but a serious public health issue. An innovative approach utilizing machine learning (ML) that incorporates features of psychological mechanisms and decision‐making characteristics related to suicidality could create an improved model for identifying suicide risk in patients with major depressive disorder (MDD). Method Forty‐four patients with MDD and past suicide attempts (MDD_SA, N = 44); 48 patients with MDD but without past suicide attempts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 104 publications
(128 reference statements)
2
8
0
Order By: Relevance
“…When they are depressive, they cannot get outside support well or cannot make effective use of support. [ 30 , 31 ] The results of previous studies [ 32 34 ] have shown that depression patients with low levels of social support increase the risk of suicide, which is more consistent with the results of this study. Therefore, for female patients with depression who live alone, attention should be paid to giving care and special attention.…”
Section: Discussionsupporting
confidence: 92%
“…When they are depressive, they cannot get outside support well or cannot make effective use of support. [ 30 , 31 ] The results of previous studies [ 32 34 ] have shown that depression patients with low levels of social support increase the risk of suicide, which is more consistent with the results of this study. Therefore, for female patients with depression who live alone, attention should be paid to giving care and special attention.…”
Section: Discussionsupporting
confidence: 92%
“…Our study’s finding that the SA group had higher psychological pain avoidance than the HSI group is consistent with those reported by Li and colleagues [25, 49]. In terms of risk decision-making, our finding that the SA group had greater loss aversion than the HSI group is similar to those from Liu and colleagues using similar methodology [44], and others employing different decision tasks or models [26, 50]. Furthermore, the SA group showed a lower estimation of the probability of balloon explosion than the HSI group, which is consistent with the results of Liu et.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the Three-Dimensional Psychological Pain theory proposed by Li and colleagues, based on the Psychological Pain theory (Shneidman, 1993), separates psychological pain into three dimensions-painful feelings, pain arousal and pain avoidance, to measure the experience, cognitive and motivation aspects of psychological pain (Li et al, 2014). Related research has found that psychological painful feelings and pain arousal were both related to suicidal ideation, while psychological pain avoidance was related to suicidal behavior (Ji et al, 2021(Ji et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Informed by these theories, a number of recent studies have focused on the process of suicide decision making, and found that after the generation of suicidal ideation, individuals often need to make repeated decisions on whether to carry out suicide (Bryan et al, 2020; Ji et al, 2021, 2022). The researchers and others have proposed that there are distinct MDD‐associated and suicidality‐associated decision‐making processes, such that there may exist unique decision biases associated with the ultimate production of suicidal behaviour, and constitute as risk factors for suicide (Ackerman et al, 2015; Gifuni et al, 2020; Perrain et al, 2021).…”
Section: Introductionmentioning
confidence: 99%